Analysis of control methods for boost DC-DC converter - Fadzlan Nisha, Muhamad Nasharudin (2012)
Boost converter is one of the types for power converters and inherently very nonlinear circuit due to the switching characteristics in the switching device. In this project, the performance of the output boost converter is analyzed by applies the proportional integral derivative (PID), two-level hysteresis and three level hysteresis controller. All simulation works are done by using MATLAB Simulink software. This project investigates and develops all three controllers and makes a comparison performance among these controllers. The comparisons are taking into account the transient response and load changes of the boost converter. It is show that the PID controller and hysteresis controller has a trade-off performance between the load changes and start-up transient response.